Endoscopic management of non‐anastomotic biliary strictures following liver transplantation: Long‐term results from a single‐center experience. Issue 5 (8th December 2020) - Barbaro, Federico; Tringali, Andrea; Larghi, Alberto; Baldan, Anna; Onder, Graziano; Familiari, Pietro; Boškoski, Ivo; Perri, Vincenzo; Costamagna, Guido
Abstract : Objectives: Studies on endoscopic treatment of non‐anastomotic biliary strictures (NABS) following orthotopic liver transplantation (OLT) are scanty and with a short follow‐up. The long‐term results of endoscopic treatment with plastic stents of NABS following OLT were analyzed. Methods: Retrospective analysis of consecutive enrolled patients who underwent endoscopic treatment for NABS after OLT between 1997 and 2015. Endoscopic treatment success was defined as stricture resolution, without recurrence. Results: During the study period, 33 patients with NABS underwent endoscopic retrograde cholangiopancreatography (ERCP) in our center. A total of 68 ERCP were performed with a 4.4% of procedure‐related adverse events. Mortality related to cholangitis secondary to endoscopic procedures was 12%. After median follow‐up of 70.3 months from stents removal, NABS resolution was obtained in 12 out of 24 (50%) patients. Only one case of late NABS recurrence was observed which was successfully retreated endoscopically. According to our data analysis NABS occurring <12 months from OLT showed a worse prognosis ( P < 0.04). Conclusions: The follow‐up of this study confirms that endoscopic treatment of NABS is unsatisfactory. However, patients who respond to endoscopic treatment maintain the response over time. Prompt treatment of acute cholangitis due to stents occlusion is advised in these patients to avoid high mortality rates.